Manifestations of Speech Aggression in the Creativity of "Literaturnaya Gazeta" Television Criticists (Russia) - Bakanov, Roman P. (Journal of History Culture and Art Research, 2017)
The article investigates the examples of verbal aggression manifestations in publicistic texts that assess the modern broadcasting practice and the content of the main Russian television companies, "Literaturnaya gazeta", one of the popular weekly periodicals in Russia. In each issue of this newspaper, several articles were published with an assessment of the quality of television broadcasts. Having studied the archives of "Literaturnaya gazeta" issues (260 in total) for the period of 2012-2016, we found 842 articles containing both positive and negative evaluations of TV shows, the work of the TV show hosts and the trends of modern federal television broadcasting. Using the methods of "Literaturnaya gazeta" continuous monitoring, a quantitative and a content analysis of its articles and the comparison of the articles of television critics published in different years, we found out that a large part of the analyzed articles, the thing was about television programs and famous persons taking part in them. Having analyzed the style of information presentation in the publications of television critics of "Literaturnaya gazeta", we found out that verbal aggression over the chronological period of the research was one of the frequently used methods to develop a negative public opinion about the practice of the main Russian television channel functioning. In 2012-2016 this language phenomenon was applied in relation to television programs, television personalities and to characterize a social-political situation in the country where Russian television operates. We believe that the regular appeal of critics to verbal aggression testifies to the desire of "Literaturnaya gazeta" authors to influence the audience more emotionally than rationally and follow a simple path, revealing and replicating the negative.